Pengaruh Literasi Dan Lingkungan Keluarga Terhadap Berpikir Kritis Siswa/Mahasiswa - Dea Meliana (CV. ITTC INDONESIA, 2025)
This research aims to explore the influence of literacy and family environment on the critical thinking abilities of pupils and students in Indonesia. Using the literature study method, data was collected from relevant articles published in the last ten years through databases such as Google Scholar, Science Direct, and Google Scholar. The research results show that the low interest in reading in Indonesia, which is reflected in only 0.001% of the population having the habit of reading, has a negative impact on the critical thinking abilities of the younger generation. Several factors that influence this low interest in reading include a lack of reading habits from an early age, unequal access to education, and minimal book production. The family environment plays an important role in forming children's literacy habits, where parents as role models have the responsibility to instill an interest in reading. This research confirms that low literacy contributes to limited critical thinking abilities, so joint efforts are needed from families, schools and communities to improve literacy culture. By instilling the habit of reading from an early age and improving access and quality of educational facilities, it is hoped that pupils and students' critical thinking abilities can develop optimally.